You are on page 1of 4

# Unit no: 1

EXERCISE 1.1

3 3 4
2 3 4
0 1 1

3. A =

A .I

3 3 4
2 3 4
0 1 1

A3 A1

6. A =

7. A =

1 2 2

2 1 2
2 2
1

3 AT

2 1
1 2 ,
3 1 2 2

A1 AT

9. A= 1 2

1.2
3.x + y + z = 9, 2x+5y+7z = 52, 2x+y-z=0
4.2x-y+z =7, 3x+y-5z =13, x + y + z= 5
5.x-3y-8z+ 10=0, 3x+y =4, 2x+5y+6z = 13
1.4
(4)x+y+z =4, x-y+z = 2, 2x+y-z=1
(5)2x+y-z=4, x+y-2z =0, 3x+2y-3z =4
(6)3x+y-z =2, 2x-y+2z = 6, 2x+y-2z =-2
(7)x+2y+z = 6, 3x+3y -z =3 , 2x+y-2z = -3
(8)2x-y+z = 2, 6x-3y +3z =6, 4x-2y+2z = 4
(9) 1

3 2 2
2 4 1
2 1
1 , 5 , 0
x y z
x y z
y z

(10)

1.5
1(i) 4x+3y+6z = 25, x+5y+7z = 13, 2x+9y+z = 1
(ii)x-3y-8z = -10, 3x+y-4z = 0, 2x+5y+6z -13=0
(v) x+y-z = 1, 2x+2y-2z = 2, -3x-3y+3z = -3

2.
3. k

## x+y+z = 2, 2x+y-2z =2,

kx+y+z = 1, x+ky+z = 1, x+y+kz = 1 (i)

x+y+4z =2.
(ii)

(iii)

1.4:
A = 1 1
1
1
2 3 ,
2 1 3

AI

1.8:
1.18:(1) x+2y+z = 7, 2x-y+2z = 4, x+y-2z = -1
(2) x+y+2z = 6, 3x+y-z = 2, 4x+2y+z = 8
(4) x+y+2z = 4, 2x+2y+4z = 8, 3x+3y+6z = 12
1.19:
1.21:
1.22:
1.23:
1.24:
1.25:
5, 2x-2y+2z = 10.

## . x+y+2z = 0, 3x+2y+z = 0, 2x+y-z = 0.

2x+5y+7z = 52, x+y+z = 9, 2x+y-z = 0.
2x-3y+7z = 5, 3x+y-3z = 13, 2x+19y-47z = 32
x+y+z = 6, x+2y+3z = 14, x+4y+7z = 30
. x-y+z = 5, -x+y-z = -

1.26:

## x+y+z = 6, x+2y+3z =10, x+2y+

z=

(i)

(ii)

(iii)
1.27:

1.28:

x+y+3z = 0, 4x+3y+

## x+2y-5z = 0, 3x+4y+6z =0, x+y+z = 0

z =0, 2x+y+2z = 0

(ii)

Unit no:2
cos(A+B) = cosA cosB sinA sinB
Sin(A-B) = sinAcosB cosAsinB

2.2 4.
2.4 7.

2.5

5.

a 2 i 3 j k ,

12.

a i j k , b 2 i k , c 2 i j k , d i j 2k

a ( b c ) ( a c ) b ( a b ) c

b 2 i 5 k, c j 3 k

( a b ) ( c d ) a

2.7
3.

x 1
y 1
z

1
1
3

7.

x2
2

8.

(1, 3, 2)

x 1
y2
z 3

2
1
3

9.

(-1, 3, 2)

x+2y+2z=5

y2
3

x2
y 1
z 1

1
2
1
x 1

z 1
3

3x+y+2z=8

2.8
y 1

z 1
1

x2

y 1

z2
2

d c a

c d

10.

A(1, -2, 3)

11.

(1, 2, 3)

B(-1, 2, -1)

(2, 3, 1)

3x-2y+4z-5=0

x2
y2

2
3

12.

x2
y 1
z 1

2
3
4

z 1
2

(-1, 1, -1)

3i 4 j 2k , 2 i 2 j k

13.

7ik

14.
2.16:
2.17:
2.29:
2.44:

## cos(A-B) = cosAcosB +sinAsinB

sin(A+B) = sinAcosB +cosAsinB

x 1

y 1
z 1

1
0

x4

z 1
3

2.50:

x2
y 1
z 3

3
2
4

2.51:(-1, 1, 1)
2.52:

x 1
y 1
z2

2
3
2

(1, -1, 1)

## (2, 2, -1), (3, 4, 2)

x+2y+2z = 5
(7, 0, 6)
Unit no: 3

3.2
(8)

(i)

z-

(iii)

z-

(v)

z-

z 1
Re
1
z i

(5)

y n y n
n 1 sin n

q

sin n

x 2 2x 4 0

n n i 2 n1 sin
(8)

1
2 cos
x

(i) x m

n
3

and

abc

(i)

9 9
y

1
2 cos
y

(ii) x m
yn
yn
2 cos(m n )
m 2i sin( m n )
m
n
x
y
x

a cos 2 i sin 2 ,

(10)

3.4

q
tan
y p
(6)

z 1
arg

2
z 3

x 2 px ( p q ) 0
2

2z 1
Im
2
iz 1

2 cos( )

abc

c cos 2 i sin 2

b cos 2 i sin 2
2

c2
2 cos 2( )
abc

(ii) a b

3.5
1.

(iii)

(4).

: (ii)

(5)

2 i

3.11:
(i) P

3 i)

2
3

x 4 x3 x 2 x 1 0
3

3
2

(ii) P

z,

z 1
Re
1
z i

z 1
arg

3
z 1

3.22:

,
3.23:
3.25:

x2 2x 2 0

cot y 1,

x9 x5 x 4 1 0
(

3 i)

( y )n ( y )n
sin n

sin n

3.24:

x 7 x 4 x3 1 0

2
3

Unit no: 4
4.1.
2

## (iv) y +8x-6y +1=0

(v) x2-6x-12y-3=0
5.

40

5
30
4.2.

## 5. (ii) x2 +4y2-8x-16y -68 = 0

(iv) 16x2 +9y2 + 32x-36y = 92
7.

6
8.

1
2

(i)

(ii)
40

16

9
4.3
5. (ii) x2 -4y2+6x+16y 11 = 0
(iv) x2 -3y2 + 6x+6y +18 = 0
4.4
x2-9y2 = 9
x2+3y2=12

5. 5x+12y = 9
6. x-y+4=0

4.5
2) (ii)

(2,4).

(2,0)

4.6
3) x+2y-5=0
EXERCISE 4.5
1.
8x2+10xy-3y2-2x+4y-2= 0
4x+3y-7 = 0
x-2y = 1
5.

x+2y-12=0

(6, 0)

x-2y+8=0

(-3, 0)

(2, 3)

(2, 1)

(1, -1)

3x-y-5 = 0

EXERCISE 4.6
(iii) 6x2+5xy-6y2+12x+5y+3 = 0
Example 4.64: 3x2-5xy-2y2+17x+ y+14=0
4.7:
(iv) y2-8x+6y+9=0
(v) x2-2x+8y+17=0
4.8:

4.10:

4.12:

4.13:

comet)

sun),

(i)

(ii)

4.14:

4.31:
4.32:
4.33:

(iv) 36x2+4y2-72x+32y-44=0
?

4.35:
P
4.56:

9x2-16y2-18x-64y-199 = 0

4.57:

9x2-16y2+36x+32y+164 = 0
Unit Test: 5

5.6

14.7
x = 9.8t- 4.9 t

(i)

( ii )
5.7

10

1 /
6

5.8:

50

60
A

B
5.9.

5.1.
1.

t
(i)
(iv)

3.

x = 100t - 25 2
t
2

(ii)
(Break)

(iii)
t

x = 20 t - 5
3

(i)

9.

(ii)

t2

B
8.

## x a( sin ), y a(1 cos )

5.13 :

x1 2

5.14:

16 x 2 9 y 2 144

5.15:

x a cos , y b sin
2

5.17:
5.18:
5.20:

y1 >0

( x1 , y1 )

y=x

y= (x -2)

ax 2 by 2 1, a1 x 2 b1 y 2 1

x a cos 4 , y a sin 4 , 0

a
5.2
5.

x 2 y 2 52

7.

y x3

2x+3y=6
P

x a cos 3 ; y a sin 3

x cos

y sin a cos 2

xy k

y2 x

8k 2 1
5.5

## lim (cot x) sin x

5.34:

lim ( x) sin x

5.35:

x 0

x 0

5.6 (11)
lim (tan x) cos x

x
2

5.48(a):
5.51:

f ( x) x 2 sin x, 0 x 2

f ( x) x 4 3 x 3 3 x 2 x
5.9

(3)

(iii) x4-6x2
(iv) (x2-1)3
(v) sin 2 ,

0,

(vi) t+cost
5.52:
2400

y 2 2x

5.53:
5.54:
5.55:

5.56:

(1, 4)

8
27

5.57:

5.58:
Q

,
R

Q
/

S
Q
5.10

3.
4.
r
5.63:

y x 4 4x 3
5.64:

y ex

,
5.11

5.

f ( x) x 6 x
f ( ) sin 2 ; (0, )

6.

y 12 x 2 2 x 3 x 4

4.

8
Q